2002
DOI: 10.1097/00004728-200209000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic MRI After Surgical Repair for Pelvic Organ Prolapse

Abstract: Dynamic MRI is helpful in the evaluation of persistent patient complaints after surgery for pelvic organ prolapse and detects more defects than physical examination does.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…In our study group dysfunction in the middle compartment was associated in most cases with pathology in neighboring compartments, especially the posterior wall, as shown by Gufler et al. (10,18). Maybe this caused the significant difference of enteroceles assessed in our study using these two methods (dMRI revealed 2.5 times more defects than CE).…”
Section: Discussionsupporting
confidence: 78%
“…In our study group dysfunction in the middle compartment was associated in most cases with pathology in neighboring compartments, especially the posterior wall, as shown by Gufler et al. (10,18). Maybe this caused the significant difference of enteroceles assessed in our study using these two methods (dMRI revealed 2.5 times more defects than CE).…”
Section: Discussionsupporting
confidence: 78%
“…There is general agreement that MRI of the pelvic floor should encompass static and dynamic MR images, whereas dynamic means imaging under maximum stress to the pelvic floor and MR defecography. Static MR images visualize pelvic floor anatomy and defects of the supporting structures, while dynamic MR images visualize pelvic organ mobility, pelvic floor weakness, pelvic organ prolapse (POP) and associated compartment defects [ 5 , 8 11 ]. Additionally, MRI may diagnose unexpected underlying masked functional abnormalities, which might be discrepant from the dominant symptom and may influence the choice of the surgical technique in around 42 % of patients with different spectra of PFD [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…urogynecologists, urologists, surgeons) in a single patient. It offers the advantage of visualization of POP without overlapping, regardless of the extent of the prolapse or which compartment is involved (8,(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…So far, follow-up assessment after reconstructive surgery using dynamic MRI has been performed in only a few studies, although dynamic MRI may have the potential to visualize the therapeutic outcome after surgery and may determine re-prolapse at an earlier date (14,24,27). Nevertheless, in this study and in all the studies known to the authors that have been published in this field, the meshes themselves cannot be visualized by MRI.…”
Section: Discussionmentioning
confidence: 99%